Absorption, distribution, metabolism, and excretion of [14C]sesamin in rats. Issue 8 (6th February 2017) - Tomimori, Namino; Rogi, Tomohiro; Shibata, Hiroshi
Abstract : Sesamin is a major lignan in sesame seeds and has various physiological effects. Sesamin is absorbed efficiently and distributed over the whole body. In particular, sesamin is highly distributed in the form of its metabolites in the liver and kidney. The various physiological effects of sesamin may be due to the action of its metabolites. Abstract : Scope: Sesamin is a major lignan in sesame seeds and has various physiological effects. Although metabolism of sesamin by cytochrome P450 or intestinal microflora has been reported, little is known concerning the mass balance, pharmacokinetics, and tissue distribution of sesamin. Methods and results: Absorption, distribution, metabolism, and excretion of [ 14 C]sesamin were investigated after a single oral dose of 5 mg/kg in rats. Sesamin was absorbed with peak plasma radioactivity at 1.0 h and declined with a terminal half‐life 4.7 h. The cumulative excretion of radioactivity was 37.5 ± 3.1% in urine and 58.7 ± 4.8% in feces. In bile duct‐cannulated rats, the cumulative excretion of radioactivity was 66.3 ± 8.4% in bile and 27.8 ± 10.2% in urine. Tissue distribution was investigated using quantitative whole‐body autoradiography. Radioactivity was widely distributed over the whole body and was highly detected in the liver and kidney. The metabolites profile was examined using radiochromatography. Sesamin was mainly distributed in the form of conjugate metabolites. Conclusions: Sesamin was absorbed efficiently and distributed over the whole body. In particular, sesamin was highly distributed in the form of the metabolites in the liver and kidney. The results of this study are useful in elucidating the action mechanism of sesamin.